In watermelon sugar eaudiobook - Brautigan, Richard (Blackstone Publishing, 2017)
iDEATH is a place where the sun shines a different color every day and where people travel to the length of their dreams. Rejecting the violence and hate of the old gang at the Forgotten Works, they lead gentle lives in watermelon sugar. In this book, Richard Brautigan discovers and expresses the mood of the counterculture generation.